Execution Dualism in Corruption Cases - Mujibussalim, Teuku Herizal, Faisal A. Rani, Eddy Purnama, (Opción)
This study aims to explore the authority of criminal executors or corruption cases executors that have been enforceable on the Prosecution Office of the Republic of Indonesia by the Act Number 16, 2004 on the Indonesian Prosecution Office in its Criminal Justice System, however, since the establishment of the Corruption Eradication Commission (KPK) and the Act Number 30, 2002 as has been altered with the Act Number 19, 2019 on the KPK, it has been endowed with the same executor power towards corruption cases that have been enforceably punished, besides the power of pre-investigation, investigation and charge. Thus, KPK as the institution has a huge power to combine its great function in one of the influential institution in the state structure which causes dualism execution power of conviction of the Prosecution Office of the Republic of Indonesia and the KPK in integrated criminal justice system which exempting the principle of dominus litis (prosecution office as the criminal case controller), the principle of een on deelbaar (one prosecution office) and the prosecution office is the only implementing institution of criminal conviction (executive ambtenaar) through juridical formal. This study based on court decision on corruption convictions which causes not effectitive its execution of corruption cases such as lacks of rules in the Act Number 31, 1999 as has been amended with the Act Number 20, 2001 on Corruption Suppression such as money as repalecemnt fine is not paid by the convicted and companies, conviction towards corporations for instance license termination or cancel its company license that its power only owned byy the Prosecution Office and not owned by the KPK as ruled by Article 32 of the Act Number 16, 2004 and clearly stipulates in Acrticle 146 (1) of the Act Number 40, 2007 on Liminted Company which states that the First Instance Court can abolish the Limited Company on the prosecution office application based on the company reason violating public interest or laws, hence it requires consstennt and integrated power in implementing execution of the conviction its dualism of similar execution at two different institutions with the standard and different methods to execute the convictions can be settled through coordination in the in tehrated criminal jstice system that controls each other and performs check and balance under the supervision of the Prosecution Office of the Republic of Indonesia.